Sustainable weed management in rice to ensure food security: a review - Motmainna, Mst; Juraimi, Abdul Shukor; Che’Ya, Nik Norasma; Mat Su, Ahmad Suhaizi; Mazlan, Norida; Abd Manaf, Muhamad Noor Hazwan; Ramli, Zaid; Hasan, Mahmudul (American Chemical Society, 2025)
Globally, food security has become a severe issue with the increase in world population. Infestations of weeds are well acknowledged as a significant biological constraint to crop yield across the agroecosystems and seasons. However, high labor costs have led to a decline in the use of conventional manual weeding methods, and this trend has been mirrored worldwide by an increase in synthetic herbicides. Continuous use of synthetic herbicides increases the possibility of herbicide resistance, contaminated agricultural goods, and adverse impacts on environment and human health. Because of these issues, researchers are now interested in finding alternatives to synthetic herbicides. There is no single effective solution for combating weeds; therefore, this review focuses on developing and implementing more sustainable weed management that involves cultural, mechanical, and biological weed control, and efficient chemical herbicides and artificial intelligence. The review synthesizes findings from a wide range of peer-reviewed studies, case reports, and agricultural extension documents. By examining the current state of sustainable weed control, this review offers valuable insights for both conventional and organic growers seeking to manage weed populations while minimizing environmental impact. Ultimately, it aims to contribute to global food security by promoting more resilient and sustainable agricultural practices.